L’accent préfère-t-il le sens ? Les noms féminins en -ess en anglais britannique contemporain - Jérémy Castanier (Corela)
Within a dynamic synchronic approach using in particular all 18 editions of the English Pronouncing Dictionary, this study examines the emergence since the mid-20th century of final stress in British English (but not in American English) on feminine nouns in -ess (authoress, shepherdess, actress, manageress, etc.), whereas this ending used to be perfectly stress-neutral. The situation seems confusing, since 41% of the 78 contemporary feminine nouns in -ess now accept final stress as their main or variant pattern. When unstressed, the final syllable also oscillates between a full vowel [-es] and a weak vowel [-ɪs/-əs].We show that morphology plays a fundamental role in this new pattern, depending whether the masculine or neutral deriving forms and the feminine derivatives are parisyllabic (stress is usually not shifted: ‘actor > ‘actress) or imparisyllabic (final stress is frequent: ‘author > ˌautho’ress). We also show that this ending may have a marked meaning, and that this semantic criterion interacts with the morphological criterion in attracting stress on the final syllable or not. In the final part we try to determine the potential origins of the change by identifying its lexical diffusion pattern, which suggests the likely role of the socio-historical context (wars, feminist waves, etc.).